2009
DOI: 10.1016/j.jnt.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

On the necessity of new ramification breaks

Abstract: Ramification invariants are necessary, but not in general sufficient, to determine the Galois module structure of ideals in local number field extensions. This insufficiency is associated with elementary abelian extensions, where one can define a refined ramification filtration-one with more ramification breaks [Nigel P. Byott, G. Griffith Elder, New ramification breaks and additive Galois structure, J. Théor. Nombres Bordeaux 17 (1) (2005) 87-107]. The first refined break number comes from the usual ramificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The consideration of cyclic p-extensions of higher degree in positive characteristic is still in progress. [44], and obtained a criterion which agrees with the condition found by Miyata for certain Kummer extensions in characteristic 0 [36,133]).…”
Section: Local Galois Module Structure In Equal Characteristicsupporting
confidence: 79%
“…The consideration of cyclic p-extensions of higher degree in positive characteristic is still in progress. [44], and obtained a criterion which agrees with the condition found by Miyata for certain Kummer extensions in characteristic 0 [36,133]).…”
Section: Local Galois Module Structure In Equal Characteristicsupporting
confidence: 79%
“…In [6], it is shown that the ramification group filtration of a wildly ramified prime p is uniquely determined by the p-adic valuation of the discriminant of the field extension L/K, when both the field extension degree and the residue characteristic of p are equal to a prime number. When the Galois group is elementary abelian, the Galois module structure of certain ideals is related to the ramification group filtration, see [3,4,5]. Such a relation is investigated when the Galois group is quaternion [7], hence non-abelian.…”
Section: This Relation Is Close If An Intersection Propertymentioning
confidence: 99%
“…Of course there are many seriesα(X) with this property, but for our purposes it will not matter which we choose. Let φ : K 0 → K 0 be the p-Frobenius map and defineα ∆ (X) =α φ (X p ) and l(α) = log(α) − p −1 log(α ∆ ), where log(1 + ψ(X)) = ψ(X) − 1 2 ψ(X) 2 Proof: By the linearity and continuity of the Kummer pairing we may assume that…”
Section: Kummer Theorymentioning
confidence: 99%
“…If i 1 = p 2 b−pb then b * can take any of the values allowed by Theorem 5 in[2]. On the other hand, for a given b * we have eitheri 1 = p 2 b−pb or i 1 = b * +p 2 b−pb−b.…”
mentioning
confidence: 99%